A sign of the times - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
An agroforestry demonstration project in Kenya, which ran from 1993-1996, set out to promote ecologically sustainable agricultural practices in the Mount Kenya region. A network of demonstration farms was established, and they still serve as the...